Pro Web 2.0 Application Development with GWT - Dwyer, Jeff (Apress, 2012)
This book is for people who are looking to get beyond small proof-of-concept sample applications. It’s for people who want to see what the guts of a full-fledged GWT application should look like. Perhaps you’ve already been convinced that GWT is a technology worthy of your attention. You’ve certainly read some simple tutorials and comparisons of frameworks, and you’re familiar with the pros and cons.